Bridging Pedagogy and Practice: Case-Based Learning and Mind Maps. - Kleinhans, Kelly; Richards, Courtney; Desomma, Alison (Perspectives of the ASHA Special Interest Groups, 2025)
Purpose: This clinical focus article discusses the use of mind maps in casebased learning (CBL) for teaching students studying speech-language pathology. The purpose is to explain how to incorporate this inquiry-based pedagogical method for clinical teaching as a means to improve understanding and organization of complex information and practice clinical decision making. By describing the theoretical underpinnings and practical applications of CBL and mind maps, this article provides a comprehensive framework for educators to effectively implement these strategies in their courses. Conclusions: Implementing CBL and mind maps in speech-language pathology education offers significant advantages in fostering active learning and student engagement. The combined use of these strategies promotes a deeper understanding of clinical concepts and facilitates the application of theoretical knowledge to real-world scenarios. This article concludes that adopting a structured approach to integrating CBL and mind maps can lead to improved educational outcomes and better prepare students for clinical practice. Practical guidelines are provided to assist teachers in incorporating mind maps using CBL into their teaching repertoire.